Sepia Melanin-Loaded Primary Human Gingival Keratinocytes: An In Vitro Model for Studies on Pigmented Gingiva - Shilpi Goenka (MDPI AG, 2023)
The objective of this study is the development of an in vitro cell culture model of pigmented gingival keratinocytes to provide a unique tool to assess oral care products such as toothpaste and evaluate whether pigmented gingival cells might be less susceptible than unpigmented cells to cytotoxicity by any toothpaste. Sepia melanin at various concentrations was added to primary human gingival keratinocyte (HGK) monolayers to identify the concentration at which melanin is sufficiently phagocytosed in the absence of cytotoxicity; this concentration was subsequently used to generate pigmented HGK model. Extracts from three commercial adult toothpastes (Crest 3D White, Sensodyne, and Colgate Optic) at different dilutions were evaluated in pigmented and unpigmented HGKs for cytotoxicity over a 24 h duration by MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] assay. Results demonstrated that HGKs showed a concentration-dependent uptake of sepia melanin with a significant linear correlation of pigment uptake. Moreover, the melanin was distributed perinuclearly in the cells, that was similar to the distribution of physiological gingiva in vivo. Further experiments were conducted with 25 µg/mL sepia melanin as higher concentrations induced cytotoxicity. Evaluation of three commercial toothpastes on unpigmented and pigmented HGKs showed no differential effects at any dilution. In summary, a model of pigmented HGKs with the ability to create a controlled level of pigmentation was demonstrated. Examination of extracts from three commercial toothpastes revealed similar cytotoxicity to both pigmented and unpigmented HGKs. In conclusion, this study shows that the artificially pigmented HGK model is an easy and low-cost tool that mimics the in vivo gingival pigmentation. Moreover, the evaluated toothpastes showed similar cytotoxicity to pigmented and unpigmented HGKs, suggesting that the presence of melanin did not impart any protective effects. Further studies to employ this pigmented HGK model to evaluate a large number of oral care products and include repeated exposures and longer duration are warranted.